How children "add" or "restrict" entities and temporal spans in narrations: evidence from Italian and English native children - Giuliano, Patrizia (Linguistik Online, 2015)
This work focuses on the acquisition of restrictive and (temporal and non temporal) additive means by Italian and English native children, especially including scope particles, together with children’s progressing ability to build textual cohesion in a narrative text. In particular, the author tries to identify the age at which additive and restrictive means appear and the functions they carry out in discourse organization of very young subjects, as well as the cognitive operations the latter can use. Thanks to the consideration of two different languages, this work also explores the possible language-specific strategies exploited by the two groups of children. Part of the results can be read as age cognitive restrictions independent of the L1 of the child. Additive means appear from the age of four on but with some differences according to the types of quantification solicited, namely the quantification of entities and that of time spans: the 4-year-olds clearly have less problems in quantifying entities rather than time spans. In comparison with adult reference groups, Italian and English L1 children of any group exploit additive temporal means less frequently than means quantifying entities; the quantification of entities involving a negation shows up from the age of seven. From a cognitive viewpoint, the precocious emergence of entity contrasts by additive means is in agreement with what Givón (1995) maintains with respect to nominal referents (they are perceptually and cognitively more salient, they are acquired early in ontogeny and evolve early in phylogeny, they are culturally central entities etc.). Concerning negative particles, their later appearance is in agreement with some studies about negation showing the more problematic processing of negative structures by children with respect to the positive ones (cf. Giuliano 2004). Some other strategies identified in children’s retellings are, conversely, to be interpreted as language-specific. The more frequent problems that Italian children have with the concept of iteration with respect to English L1 children could be due to the polyfunctional semantics of the Italian particles ancora (’more, again, still’) and sempre (’always, again, still’); the late appearance of also in English L2 children’s data, an internal positioning particle, is probably caused by the fact that English has an external, perceptually more salient particle, namely too, whose semantics is equal to that of also.